Socio-demographic factors associated with smoking habits among university students in Belgrade, Serbia - Milošević Georgiev Andrijana; Kotur-Stevuljević Jelena; Krajnović Dušanka (Sciendo, 2019)
Smoking rates in Serbian adults are among the highest in Europe. The objective of this study is to assess the prevalence of smoking and smoking-related behaviours of Belgrade University students depending on their sociodemographic characteristics and faculty group.